Looking sideways to Italy in contemporary world literature - Bond, E (Routledge, 2022)
This article sketches a history of how the concept of Italy has travelled worldwide to become a mobile cultural symbol in order to show how, as a signifier, “Italy” has also become increasingly detached from any national parameters of territory. It employs a lateral method of “looking sideways” at literary representations of Italy from “outside” the national canon to show how they can put pressure on what (and where) Italian culture now resides. Analyzing three contemporary works of world literature partially set in Italy (Daša Drndić’s Trieste, Rachel Kushner’s The Flamethrowers, and Pajtim Statovci’s Crossing), it suggests that we might consider broadening out the canon of transnational Italian literature to include works neither written by Italians nor written in Italian, but that offer sideways insight into Italian history and culture from elsewhere.